2021
DOI: 10.1029/2021gl094204
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Anomalies in the Free Troposphere During the COVID‐19 Pandemic

Abstract: The reduction in the emissions of primary pollutants during the COVID-19 pandemic, due to the worldwide slowdown in economic activity, produced a perturbation in the formation of secondary compounds, including ozone, and in the oxidative capacity of the lower atmosphere. Several studies have highlighted that the sign and magnitude of the anomaly depended on the photochemical regime in the region under consideration (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…COVID-19 shutdowns in 2020 were a major perturbation to economic activity but the effect on methane is unclear. Oil/gas production declined which would be expected to decrease methane emission in some regions (Lyon et al 2021), but reduced maintenance of infrastructure could have caused increases (Laughner et al 2021).Decreases in emissions of nitrogen oxides (NO x ≡ NO + NO 2 ) from fuel combustion led to decreases in free tropospheric ozone (Bouarar et al 2021, Steinbrecht et al 2021, which would decrease OH concentrations (Miyazaki et al 2021) and hence the methane sink (Laughner et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 shutdowns in 2020 were a major perturbation to economic activity but the effect on methane is unclear. Oil/gas production declined which would be expected to decrease methane emission in some regions (Lyon et al 2021), but reduced maintenance of infrastructure could have caused increases (Laughner et al 2021).Decreases in emissions of nitrogen oxides (NO x ≡ NO + NO 2 ) from fuel combustion led to decreases in free tropospheric ozone (Bouarar et al 2021, Steinbrecht et al 2021, which would decrease OH concentrations (Miyazaki et al 2021) and hence the methane sink (Laughner et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The economic downturn due to COVID‐19 started between March and April, but the most profound anomalies can be observed around July in Europe, with a near‐symmetric anomaly structure within the year 2020 in the free troposphere that does not extend above 300 hPa. Note that Figure 10 is based on ND at each pressure level, thus the absolute magnitude of quantified 2020 anomalies is deemed to be larger in the upper troposphere than the mid‐ and lower troposphere (Bouarar et al., 2021 ), when the vertical distribution is transformed back to the units of ppbv (see Figure S17 in Supporting Information S1 ). The strongest anomalies (700‐300 hPa) above Europe occur in July with a magnitude of −4.60 ppbv (−7.5%), compared to a magnitude of −1.53 ppbv (−2.4%) in January and −1.88 ppbv (−3.1%) in December.…”
Section: Resultsmentioning
confidence: 99%
“…In general, surface observations from monitoring networks in many nations showed that urban areas with NOx‐limited regimes (e.g., Rio de Janeiro and South African urban areas) experienced ozone decreases, while urban areas with VOC‐limited regimes experienced ozone increases (e.g., urban areas in South Korea and Colombia; Sokhi et al., 2021 ). Several new attribution studies have estimated the global scale response of tropospheric ozone to the emissions reductions in 2020 (Bouarar et al., 2021 ; Gaubert et al., 2021 ; Miyazaki et al., 2021 ; Weber et al., 2020 ). These model‐based studies concluded that some regions experienced surface ozone decreases due to reduced photochemical production, while many urban areas experienced ozone increases due to lower NO emissions, which limited the ozone destruction that typically occurs in highly polluted urban centers (Sillman, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O 3 gas reduction also occurred in both cities during the LSSR phase. Some of the possibilities that cause O 3 reduction include cloudy weather conditions resulting in inhibition of the oxidation process so that O 3 formation is reduced, conditions of relative humidity and high ultraviolet radiation in tropical climates stimulate secondary particulate formations, which can inhibit O 3 production, tropical convection can also trigger O 3 reduction, and the effect of local meteorology also plays an important role in reducing O 3 when activity is restricted ( Bouarar et al, 2021 ; Qiu et al, 2021 ; Shek et al, 2022 ). With respect to anthropogenic heat and pollutant emissions, it is clear that air pollution, especially NO 2 and CO, is directly correlated with SUHII in the LSSR phase, indicating that these two pollutants support the development of SUHI in both cities.…”
Section: Discussionmentioning
confidence: 99%